Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1574-6941.2007.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing survival and efficacy of a bacterial biocontrol agent of fire blight of rosaceous plants by means of osmoadaptation

Abstract: The efficacy of Pseudomonas fluorescens EPS62e in the biocontrol of Erwinia amylovora, the causal agent of fire blight of apple and pear, depends on the colonization of plant surfaces after spray application. A procedure to increase cell survival in the phyllosphere was developed consisting of saline stress and osmolyte amendment to the growth medium during inoculum preparation. Hyperosmotic stress induced the synthesis of the osmolytes trehalose, N-acetylglutaminylglutamine amide and glucosyl-glycerol, but de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Several groups have suggested that growth and harvesting conditions also have a significant effect on the physical stability of bacteria [5558]. Sodium chloride at various concentrations was incorporated in BHI broth to determine its effect on both the growth kinetics of Ty21a as well as its development of resistance to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have suggested that growth and harvesting conditions also have a significant effect on the physical stability of bacteria [5558]. Sodium chloride at various concentrations was incorporated in BHI broth to determine its effect on both the growth kinetics of Ty21a as well as its development of resistance to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pseudomonas fluorescens EPS62e that contained higher levels of intracellular trehalose, as a response to salt stress, demonstrated higher desiccation tolerance. 266 Leslie et al 97 utilized trehalose (100 mM) to stabilize both Escherichia coli (E. coli) DH5" and Bacillus thuringiensis (B. thuringiensis) HD-1 by freeze drying. In the absence of any protectants, only 8% of E. coli and 14% of B. thuringiensis survived, whereas in the presence of 100 mM trehalose, the survival rate increased to 70% and 57%, respectively.…”
Section: Microorganisms (Bacteria Fungi)mentioning
confidence: 99%
“…P. fluorescens EPS62e was cultured, for routine use, in Luria-Bertani (LB) broth to obtain standard cells or in glucose minimal medium (GMM) plus NaCl and glycine betaine (GB) to obtain osmoadapted cells as previously described (4). To monitor culturable populations of EPS62e in the field, a spontaneous mutant resistant to nalidixic acid (EPS62e Nal r ) was selected on LB agar supplemented with 50 mg liter Ϫ1 of nalidixic acid.…”
Section: Methodsmentioning
confidence: 99%
“…A procedure of osmoadaptation based on the combination of saline osmotic stress and osmolyte amendment of the growth medium has been used to increase drought stress tolerance and improve epiphytic survival and biocontrol efficacy of the apple blue mold biocontrol agent Pantoea agglomerans EPS125 (3) and the fire blight biocontrol agent P. fluorescens EPS62e (4).…”
mentioning
confidence: 99%